THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND BULLYING BEHAVIOR AMONG FIFTH-GRADE STUDENTS OF SDN 1 GEGESIK KULON - Ria Qoriyah; Aiman Faiz; Fikriyah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aimed to determine the relationship between emotional intelligence and bullying behavior among fifth-grade students of SDN 1 Gegesik Kulon. This research used a quantitative approach with a correlational method. The sample consisted of 30 students selected through purposive sampling. Data were collected using questionnaires and analyzed using normality, linearity, and Pearson Product Moment correlation tests with SPSS. The results showed a significant negative relationship between emotional intelligence and bullying behavior. This indicates that students with higher emotional intelligence tend to exhibit lower bullying behavior. Therefore, the research hypothesis was accepted.